2018
DOI: 10.1186/s12941-018-0257-x
|View full text |Cite
|
Sign up to set email alerts
|

Continued in vitro cefazolin susceptibility in methicillin-susceptible Staphylococcus aureus

Abstract: ObjectivesIn vitro trends of cefazolin and ceftriaxone susceptibilities from pediatric clinical isolates of methicillin-susceptible Staphylococcus aureus (MSSA) between 2011 and 2016 were analyzed for surveillance.MethodsOur laboratory continues to use agar disk diffusion for staphylococcal susceptibilities applying Clinical Laboratory Standard Institute’s 2012 breakpoints.ResultsA total of 3992 MSSA clinical isolates in the last 6 years were analyzed for their in vitro cefazolin and ceftriaxone susceptibiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…As depicted in Table 1 The results revealed that some of the compounds from the series show good ABTS cation radical scanvenging activity. The compound 4i (3, showed the best ABTS activity with IC50 value of 25.31 µM, which is more active than the standards BHA, BHT and α-TOC. The compounds 4f (4-BuO) and 4j (2,3,4,5,6-F) were also sensitive to ABTS cation radical scavenging activity with IC50 values of 53.01 and 50.79 µM, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…As depicted in Table 1 The results revealed that some of the compounds from the series show good ABTS cation radical scanvenging activity. The compound 4i (3, showed the best ABTS activity with IC50 value of 25.31 µM, which is more active than the standards BHA, BHT and α-TOC. The compounds 4f (4-BuO) and 4j (2,3,4,5,6-F) were also sensitive to ABTS cation radical scavenging activity with IC50 values of 53.01 and 50.79 µM, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…As expected, the activity of the compounds increased with increasing concentration as summarized in Table 2. The compounds 4i (3, and 4k (3, showed a better CUPRAC capacity than standard α-TOC. The compound 4k had better activity at concentrations 10 and 25 µM than all three standards.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“… 34 In the perioperative setting, S. aureus remains the most common organism associated with SSI, with a majority of S. aureus isolates sensitive to first-line narrow spectrum penicillins and cephalosporins (flucloxacillin, nafcillin, cefazolin). 16 , 35 While the longstanding use of first-line penicillins and cephalosporins is routinely effective in preventing these infections, the emergence of resistance to β-lactams is challenging for SAP selection.…”
Section: Gram-positive Antibiotic Resistance Of Concern In Surgical Antibiotic Prophylaxismentioning
confidence: 99%